Development of a "Fair" Marketplace for On-Demand Capacity Matching. Issue 3 (March 2020) - Aifadopoulou, Georgia; Mallidis, Ioannis; Vlachos, Dimitrios; Salanova Grau, Josep Maria; Iakovou, Eleftherios
Variability of demand along with issues of seasonality and supply chain disruptions may lead to significant variations between the planned and required capacities of warehouse facilities. This further leads to the rise of on-demand capacity allocation issues, with supply chain stakeholders seeking to outsource their excess capacity requirements to independent warehouses. As this matching usually occurs through freight forwarders or third-party logistics operators, who may have contractual agreements with specific warehouse operators within a region, issues of bias occur with respect to the price that capacity demanders pay. In this context, this paper proposes an optimization methodology, implemented by a neutral e-marketplace, for optimizing the matches between manufacturers and warehouses under a "market-fair" contract price for both, while taking into account the market's demand/supply ratio.